Photovoltaic cell assembly capable of preventing grid from being broken

By adopting a multi-layer composite structure with a wavy sub-gate line and a microencapsulated liquid metal coating, combined with a shape memory polymer encapsulation layer and a distributed fiber sensor, the problems of insufficient mechanical reliability, optical loss and self-repair capabilities in traditional photovoltaic cell modules are solved, and efficient improvements in conductivity, mechanical strength and optical performance are achieved.

CN119698126AActive Publication Date: 2025-03-25ZHONGQING ENERGY OASIS (BEIJING) ENERGY TECH CO LTD

Patent Information

Application Number
CN202510204398.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-25
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

In traditional photovoltaic cell modules, the linear electrode gate lines have problems such as insufficient mechanical reliability, significant optical loss and lack of self-repair ability, and it is difficult to take into account the coordinated improvement of conductivity, mechanical strength and optical performance.

Method used

The sub-gate wire with a multi-layer composite structure is adopted, including an alloy conductive layer with high ductility, a conductive glue layer with a middle layer with a carbon nanotube reinforced, and a shape memory polymer encapsulation layer with a microencapsulated liquid metal coating on the surface of the sub-gate wire, and a wavy path and gradient encryption layout are designed, combining a distributed fiber sensor and a micro-stress buffer structure.

Benefits of technology

The fracture toughness and conductivity are improved, and the shape memory packaging layer is restored under temperature cycle is achieved, avoiding gate line fracture caused by thermal stress accumulation; self-repair of cracks is achieved through self-healing coating, which improves the mechanical and optical performance of the components; the distributed optical fiber sensor realizes real-time monitoring and early warning, extending the service life of the components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119698126A_ABST
    Figure CN119698126A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photovoltaic cells, in particular to an anti-grid-breaking photovoltaic cell assembly which comprises a substrate, a photovoltaic cell piece, an electrode system covering the surface of the photovoltaic cell piece and a self-repairing coating covering the surface of the thin position of the electrode system. The auxiliary grid line adopts a multi-layer composite structure and comprises an alloy conductive layer, a carbon nanotube reinforced conductive adhesive layer and a shape memory polymer packaging layer; the auxiliary grid lines are distributed in a wave-shaped path. According to the invention, the arranged auxiliary grid line is formed by compounding the alloy layer, the carbon nanotube adhesive layer and the shape memory packaging layer, so that the fracture toughness is improved under the condition that the conductivity is ensured, the shape memory packaging layer recovers deformation in temperature circulation, and grid line fracture caused by thermal stress accumulation is avoided; the arranged auxiliary grid lines are wave-shaped paths and form a gradually-changed encryption layout in the edge area of the battery piece, and the wave-shaped topological paths enable the stress borne by the grid lines to be reduced, so that the grid lines are prevented from being broken.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic cells, in particular to an anti-break grid photovoltaic cell assembly. Background Art

[0002] The surface of the silicon wafer of the solar cell is printed or deposited with a number of vertical and horizontal grid lines. The grid lines are a series of metal lines located on the surface of the cell, usually made of silver, aluminum or other conductive materials, which play the role of collecting and transmitting electrons. When sunlight shines on the silicon wafer, the silicon material converts light energy into electrical energy, generating electrons and holes. The role of the grid lines is to quickly guide these electrons to the edge of the cell so that they can be collected and used by external circuits.

[0003] Application No. CN202320871705.5 discloses a grid-breakage-proof photovoltaic cell and a grid-breakage-proof photovoltaic cell assembly, which are applied to the field of photovoltaic power generation. The assembly includes: a cell, a main grid, a secondary grid and a welding pad. The main grid is composed of at least two fine grids intersecting with the secondary grid, and the two ends of the welding pad are connected to the fine grid. During the welding process of the cell, even if the fine grid line is melted when the welding strip and the secondary grid are welded at high temperature, the grid line current will be collected to the welding strip through the fine grids intersecting with the secondary grid on both sides of the welding pad, thereby reducing the impact of the fine grid line melting when the welding strip and the secondary grid are welded at high temperature on the power generation assembly, thereby improving the assembly yield.

[0004] It can be seen that the electrode grid lines of traditional photovoltaic cells mostly adopt a linear design of a single metal material, which has the following inherent defects: insufficient mechanical reliability: the straight grid lines are prone to stress concentration under thermal cycles and mechanical loads, resulting in broken grid failure; significant optical loss: the reflectivity of the straight grid lines is generally greater than 8%, and the multiple reflection effect of the incident light cannot be effectively utilized; lack of self-repairing ability: the existing coating technology cannot actively repair microcracks when they occur, resulting in irreversible degradation of electrical performance; Although the industry has tried to alleviate the above problems through material modification, it is difficult to achieve a synergistic improvement in conductivity, mechanical strength and optical performance through a single-dimensional improvement. Therefore, a multi-dimensional innovative solution across materials, structures and functions is urgently needed to fundamentally break through the long-standing grid-break defect faced by photovoltaic modules. Summary of the invention

[0005] In order to overcome the defects in the prior art, the purpose of the present invention is to provide a grid-break-proof photovoltaic cell assembly to solve the problems raised in the above-mentioned background technology.

[0006] To achieve the above object, the present invention provides a grid-break-proof photovoltaic cell assembly, comprising a substrate: made of ultra-clear float glass, with a pyramid-shaped microstructure anti-reflection film layer on the surface; Photovoltaic cell: Monocrystalline silicon is used as the substrate, with a passivated emitter and back contact layer deposited on the surface; Electrode system: It consists of several main grid lines and several secondary grid lines connected between the long sides of the main grid lines. The secondary grid lines adopt a multi-layer composite structure, which includes an inner layer of an alloy conductive layer with an elongation rate of ≥15% and a thickness of 10-15μm; an intermediate layer of a carbon nanotube-reinforced conductive adhesive layer, with a carbon nanotube mass accounting for 5-8% and a conductivity of ≥5×10 5 S / m; the outer layer is a polycaprolactone / graphene composite shape memory polymer encapsulation layer with a thickness of 5-8μm and a phase change temperature of 50±5℃; The secondary grid lines are distributed in a wavy path, and the distance between adjacent wave peaks is 3-5 times the line width, and the amplitude to width ratio is 1.2:1 to 1.5:1; Transition layer: located between the substrate and the electrode system, composed of SiO2 nanowire arrays with a nanowire diameter of 50-100nm; Self-healing coating: Covering the surface of the secondary grid line, it contains microencapsulated Ga-based liquid metal, the capsule diameter is 10-20μm, and the rupture threshold is 12±3MPa.

[0007] As a further improvement of the technical solution, the inner layer of the electrode system is a Ag-Cu-Ni ternary alloy, wherein the Cu content is 5-8wt%, the Ni content is 2-4wt%, and the balance is Ag.

[0008] As a further improvement of the technical solution, the phase change temperature of the outer layer material of the electrode system is 45-55°C, and the shape recovery rate is ≥98%.

[0009] As a further improvement of the present technical solution, the wavy path of the secondary grid line forms a gradually encrypted layout in the edge area of ​​the cell, the peak spacing of the gradually encrypted layout changes in gradient of 10-15μm / mm, and the peak spacing in the edge area of ​​the photovoltaic cell is 60-70% of the central area.

[0010] As a further improvement of the technical solution, the middle layer of the electrode system comprises directional carbon nanotube bundles, and the arrangement direction forms an angle of ±15° with the extension direction of the gate lines.

[0011] As a further improvement of the technical solution, it also includes a micro stress buffer structure arranged at the intersection nodes of the main grid line and several auxiliary grid lines. The structure is a hemispherical protrusion with a diameter of 50-80μm and is made of a silicone rubber and silver powder composite material.

[0012] As a further improvement of the technical solution, the multilayer composite structure of the secondary grid line adopts a pulsed laser deposition process, with a laser energy density of 3-5J / cm² and a pulse frequency of 100-200Hz.

[0013] As a further improvement of the technical solution, it also includes distributed optical fiber sensors integrated in the secondary grid lines, with a sensor spacing of 2-5mm to monitor the grid line strain distribution in real time.

[0014] As a further improvement of the present technical solution, the wavy path of the secondary grid line forms a light trap structure on the light-receiving surface of the photovoltaic cell, and the path curvature radius and the wavelength of the incident light satisfy the λ / 4 phase matching condition, where λ is the wavelength of the incident light. By matching the peak wavelength of the solar spectrum, the value of λ is 500-800nm.

[0015] As a further improvement of the present technical solution, the self-healing coating is covered on the surface of the gate line by an electrostatic spraying process, with a spraying voltage of 20-30 kV, a UV curing wavelength of 365 nm, and a curing time of 10-15 seconds; the wall thickness of the microencapsulated Ga-based liquid metal is 5-8% of the capsule diameter, and the wall material comprises alternatingly stacked polyurethane layers and gas-phase SiO2 layers.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The anti-break grid photovoltaic cell assembly has a secondary grid line that is a three-layer composite of alloy, carbon nanotube glue layer, and shape memory packaging. While ensuring conductivity, the fracture toughness is improved, and the shape memory packaging layer recovers its deformation during temperature cycling to avoid grid line breakage caused by thermal stress accumulation.

[0017] 2. The anti-break grid photovoltaic cell assembly achieves self-repair of cracks through the microencapsulated liquid metal coating covering the surface of the secondary grid line, and the conductivity is restored after repair; the integrated distributed optical fiber sensor realizes real-time warning of the health status of the grid line and life prediction.

[0018] 3. The anti-break grid photovoltaic cell module has a secondary grid line that is set in a wavy path and forms a gradient and dense layout in the edge area of ​​the cell. The wavy topological path reduces the maximum stress and reduces the reflectivity through the λ / 4 phase matching light trap structure. The edge gradient and dense layout specifically suppresses the edge stress peak, thereby improving the light absorption rate in the edge area. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings described herein are only for explanation purposes and are not intended to limit the scope of the present invention in any way. In addition, the shapes and proportional dimensions of the various components in the drawings are only schematic, used to help understand the present invention, and are not specifically limited to the shapes and proportional dimensions of the various components of the present invention. Those skilled in the art, under the guidance of the present invention, select various possible shapes and proportional dimensions to implement the present invention according to specific circumstances.

[0020] Figure 1 It is a schematic diagram of the design of photovoltaic cell grid lines in conventional photovoltaic cells; Figure 2This is a front view of the overall design of the photovoltaic cell and electrode system of the present invention; Figure 3 For the present invention Figure 2 A schematic diagram of the enlarged structure at point A; Figure 4 is a longitudinal cross-sectional view of a secondary grid line of the present invention; Figure 5 is a cross-sectional view of a secondary grid line of the present invention; The meaning of each number in the figure is: 100, substrate; 200, photovoltaic cell; 300, electrode system; 310, main grid line; 320, secondary grid line; 321, inner layer; 322, middle layer; 323, outer layer; 400, self-healing coating. DETAILED DESCRIPTION

[0021] The details of the present invention can be more clearly understood by combining the accompanying drawings with the description of the specific embodiments of the present invention. However, the specific embodiments of the present invention described herein are only used for the purpose of explaining the present invention and cannot be understood as limiting the present invention in any way. Under the guidance of the present invention, the technical personnel's conception is based on any possible variation of the present invention, which should be regarded as belonging to the scope of the present invention. The terms "installation" and "connection" should be understood in a broad sense, which means direct connection and indirect connection through an intermediate medium.

[0022] The terms "central axis", "vertical", "horizontal", "front", "back", "up", "down", "left", "right", "top", "bottom", "inside", "outside" and the like used herein to indicate positions or positional relationships are based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the equipment or elements referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, in the description of the present invention, the meaning of "several" is two or more, unless otherwise clearly and specifically defined.

[0023] See also Figure 1-Figure 5 As shown, the present invention provides an anti-break grid photovoltaic cell assembly, comprising a substrate 100, a photovoltaic cell sheet 200 attached to the surface of the substrate 100, an electrode system 300 covering the surface of the photovoltaic cell sheet 200, a transition layer provided between the substrate 100 and the electrode system 300, and a self-repairing coating 400 covering the fine surface of the electrode system 300; The substrate 100 is made of ultra-clear float glass, and a pyramid-shaped microstructure anti-reflection film layer is provided on the surface; The photovoltaic cell 200 is based on single crystal silicon, with a passivated emitter and a back contact layer deposited on the surface; The electrode system 300 is composed of a plurality of main grid lines 310 and a plurality of secondary grid lines 320 connected between the long sides of the main grid lines 310. The secondary grid lines 320 adopt a multi-layer composite structure, which includes an inner layer 321 which is an alloy conductive layer with an elongation rate of ≥15% and a thickness of 10-15 μm, so as to improve the conductivity of the grid lines; The middle layer is a conductive adhesive layer reinforced by carbon nanotubes, with carbon nanotubes accounting for 5-8% by mass and a conductivity of ≥5×10 5 S / m; fracture toughness is improved; the outer layer 323 is a polycaprolactone / graphene composite shape memory polymer encapsulation layer with a thickness of 5-8μm and a phase change temperature of 50±5℃; the outer shape memory polymer encapsulation layer can recover 98% of the deformation under temperature cycling, avoiding the fracture failure of the traditional encapsulation layer caused by thermal expansion.

[0024] Specifically, the auxiliary grid lines 320 are distributed in a wavy path, and the wavy path cooperates with the pyramid anti-reflection film of the substrate 100 to reduce the light reflectivity; and the spacing between adjacent wave peaks of the auxiliary grid lines 320 is 3-5 times the line width, and the amplitude to width ratio is 1.2:1 to 1.5:1; the wavy topological path reduces the stress concentration factor; The transition layer is composed of a SiO2 nanowire array, and the nanowire diameter is 50-100nm; the transition layer SiO2 nanowire reduces the thermal stress mismatch rate; The self-healing coating 400 comprises microencapsulated Ga-based liquid metal, the capsule diameter is 10-20 μm, and the rupture threshold is 12±3 MPa. When a grid line crack occurs, the microcapsule coating releases liquid metal, that is, when the stress is ≥12 MPa, and the conductive performance is restored after repair.

[0025] Furthermore, the inner layer 321 of the electrode system 300 is a ternary alloy of Ag—Cu—Ni, wherein the Cu content is 5-8wt%, the Ni content is 2-4wt%, and the balance is Ag.

[0026] Furthermore, the phase transition temperature of the material of the outer layer 323 of the electrode system 300 is 45-55° C., and the shape recovery rate is ≥98%.

[0027] Specifically, the wavy path of the secondary grid line 320 forms a gradually densified layout in the edge area of ​​the cell, the peak spacing of the gradually densified layout changes by a gradient of 10-15 μm / mm, and the peak spacing in the edge area of ​​the photovoltaic cell 200 is 60-70% of that in the central area; The formation of a gradual densification layout refers to increasing the peak density of the wave-shaped path in a specific area, that is, reducing the distance between adjacent peaks, thereby increasing the grid line coverage density in the area; and the peak distance gradually decreases from the central area to the edge area of ​​the photovoltaic cell 200; Example description: The peak spacing in the central area is 5 times the grid line width, such as a grid line width of 30μm and a spacing of 150μm; Edge area peak spacing: 3 times the grid line width, spacing 90μm; The gradient of the spacing change in the transition area: the spacing is reduced by 10-15μm per millimeter of length; Using topology optimization algorithms, such as variable density method, to minimize stress concentration factor and maximize light absorption efficiency as objective functions, a wavy path with gradient changes is generated; Finite element analysis (FEA) shows that the encrypted layout reduces the peak stress in the edge area from 180MPa to 75MPa, a decrease of 58%.

[0028] It is worth noting that the shape of the secondary grid line 320 solves the following core problems: Mechanical stress problem: The edge of the photovoltaic cell 200 is subjected to greater mechanical stress during installation and thermal cycling. The dense layout disperses the stress to more wave crest nodes by increasing the grid line density; shortens the stress transfer path by reducing the wave crest spacing, and reduces the risk of fracture. Optical performance issues: Micro cracks are easily generated in the edge area due to shrinkage of packaging materials. The dense layout enhances the light trapping effect through more wavy structures to compensate for the light loss caused by cracks. The gradual design avoids sudden changes in optical performance and maintains the uniformity of the overall efficiency of the component. Electrical performance issues: The edge current density is high. The dense layout can increase the number of secondary grid lines and reduce the lateral resistance. The wavy path can be used to extend the conductive channel and balance the uniformity of current distribution. Experimental data comparison: Mechanics: edge stress is reduced by 58% and the ability to resist gate breakage is improved; Optics: light trapping effect is enhanced and edge reflectivity is reduced by 66%; Electrically: current distribution is uniform and fill factor is increased by 5%; through gradient encryption and wave-shaped collaborative design, cross-dimensional optimization of stress-optical-electrical performance is achieved in the photovoltaic field.

[0029] Furthermore, the middle layer 322 of the electrode system 300 includes directional carbon nanotube bundles, and the directional arrangement and the gate line extension direction form an angle of ±15°; the directional arrangement of the carbon nanotube bundles improves the carrier mobility.

[0030] In addition, it also includes a micro stress buffer structure arranged at the intersection of the main grid line 310 and several auxiliary grid lines 320. The structure is a hemispherical protrusion with a diameter of 50-80μm, and the material is a composite material of silicone rubber and silver powder; it is conducive to improving the fatigue life of use; it also includes a distributed optical fiber sensor integrated in the auxiliary grid line 320, the sensor spacing is 2-5mm, and the grid line strain distribution is monitored in real time; The Φ80μm polyimide coated optical fiber is used, which is temperature-resistant from -60℃ to 300℃, and the core is doped with GeO2 to improve the Rayleigh scattering sensitivity. The optical fiber is fixed in the middle layer of the secondary grid line 320, that is, in the carbon nanotube conductive adhesive layer, in a spiral winding or parallel embedding manner, with a spacing of 2-5mm. The two ends of the optical fiber are connected to a demodulator with a wavelength resolution of 1pm and a sampling rate of 10kHz, and the signal line is led out through the photovoltaic module junction box. Sensing mechanism: Based on optical frequency domain reflectometry (OFDR) technology, the grating line strain causes micro-bending of the optical fiber, resulting in a Rayleigh scattering spectrum shift of Δλ∝ε, and the strain resolution reaches 1με; Temperature compensation: The optical fiber has built-in FBG, i.e., fiber Bragg grating reference point, to eliminate the cross sensitivity of temperature to strain measurement.

[0031] Specifically, the multi-layer composite structure of the secondary grid line 320 adopts a pulsed laser deposition process, with a laser energy density of 3-5J / cm² and a pulse frequency of 100-200Hz; it is used to achieve an interlayer bonding strength of ≥200MPa, which is higher than the traditional screen printing process; The wavy path of the secondary grid line 320 forms a light trap structure on the light-receiving surface of the photovoltaic cell 200, and the path curvature radius and the wavelength of the incident light meet the λ / 4 phase matching condition, where λ / 4 means that the light wave propagation path difference or the medium thickness is one quarter of the wavelength; λ is the wavelength of the incident light, and by matching the peak wavelength of the solar spectrum, the value of λ is 500-800nm; The phase matching principle is: When a light wave is reflected at an interface, if the optical path difference of the reflection path satisfies Δ=λ / 4, the phase difference between the two reflected light beams is π (180°), resulting in destructive interference, thereby greatly reducing the reflectivity.

[0032] Specifically, the curvature radius (R) of the wavy grating line of the present invention is designed to be R = λ / 4 (for the target wavelength λ), so that the incident light forms phase matching interference between the multiple reflected lights on the grating line surface; the reflection path difference of the light wave at the adjacent peaks and troughs of the secondary grating line 320 is λ / 2, and the corresponding phase difference is π, resulting in destructive interference; The unabsorbed reflected light is confined within the wavy grooves, forming multiple internal reflections, which increases the probability of photon absorption; Comparison with traditional technology: Take λ=600nm (yellow light) as an example: The curvature radius of the designed gate line wave path is R=600 / 4=150nm; The reflected optical path difference of the incident light on adjacent curved surfaces is 2×R=300nm=λ / 2, and the phase difference is π; After the reflected light waves are superimposed, their amplitudes cancel each other out and the reflected energy is reduced to the theoretical minimum value.

[0033] In addition, the self-healing coating 400 is coated on the surface of the grid line by an electrostatic spraying process, with a spraying voltage of 20-30 kV, a UV curing wavelength of 365 nm, and a curing time of 10-15 seconds; the wall thickness of the microencapsulated Ga-based liquid metal is 5-8% of the capsule diameter, and the wall material includes alternately stacked polyurethane layers and gas-phase SiO2 layers; The specific steps of spraying the self-repairing coating 400 include: Pretreatment: Plasma cleaning of the grid line surface, argon atmosphere, power 100-150W, time 30-60 seconds, to improve surface energy and enhance coating adhesion; Spraying parameters: Spraying material: microencapsulated Ga-In-Sn liquid metal, capsule diameter 10-20μm, wall material is polyurethane / silicon dioxide composite shell, suspended in epoxy resin base liquid, solid content 25-30%; Electrostatic voltage: 20-30 kV, spray gun distance 50-80 mm, atomizing air pressure 0.3-0.5 MPa; Curing process: UV irradiation, wavelength 365nm, intensity 500-800 mW / cm², time 10-15 seconds, to make the epoxy resin quickly cross-linked into a film.

[0034] Among them, the self-repairing coating 400 spraying process has the following characteristics: Low-temperature lossless encapsulation: The low-temperature characteristics of electrostatic spraying prevent microcapsules from rupturing. The traditional thermal spraying process temperature > 150°C will destroy the capsule structure; Directional coverage: The distribution of microcapsules is controlled by electric field, so that the enrichment of liquid metal capsules on the surface of the secondary grid line 320 reaches more than 80%; Nano-scale density: UV curing forms a dense protective layer with a thickness of 200-300nm and a porosity of <0.5%.

[0035] The test data of self-healing coating 400 are as follows: Through the process innovation of directional spraying and low-temperature curing, combined with the coordinated design of microcapsule structure and grid line morphology, the present invention avoids the defects of traditional processes while ensuring the self-repair function, forming a full-chain technology improvement from material formulation to manufacturing equipment.

[0036] It should be noted that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A photovoltaic cell assembly with an anti-breaking grid, characterized in that: It comprises a substrate (100): made of ultra-white float glass, with a pyramid-shaped microstructure anti-reflection film layer on the surface; Photovoltaic cell (200): with single crystal silicon as substrate, and a passivated emitter and a back contact layer deposited on the surface; The electrode system (300) is composed of a plurality of main grid lines (310) and a plurality of secondary grid lines (320) connected between the long sides of the main grid lines (310), wherein the secondary grid lines (320) adopt a multi-layer composite structure, including an inner layer (321) being an alloy conductive layer with an elongation of ≥15% and a thickness of 10-15 μm; an intermediate layer being a carbon nanotube-reinforced conductive adhesive layer, wherein the carbon nanotubes account for 5-8% by mass and have a conductivity of ≥5×10 5 S / m; the outer layer (323) is a polycaprolactone / graphene composite shape memory polymer encapsulation layer with a thickness of 5-8 μm and a phase transition temperature of 50±5°C; The secondary grid lines (320) are distributed in a wave-shaped path, and the distance between adjacent wave peaks is 3 to 5 times the line width, and the ratio of amplitude to width is 1.2:1 to 1.5:1; Transition layer: provided between the substrate (100) and the electrode system (300), and composed of a SiO2 nanowire array, with a nanowire diameter of 50-100 nm; Self-healing coating (400): covers the surface of the secondary grid line (320), contains microencapsulated Ga-based liquid metal, the capsule diameter is 10-20 μm, and the rupture threshold is 12±3 MPa.

2. The anti-break grid photovoltaic cell assembly according to claim 1, characterized in that: The inner layer (321) of the electrode system (300) is a ternary alloy of Ag-Cu-Ni, wherein the Cu content is 5-8wt%, the Ni content is 2-4wt%, and the balance is Ag.

3. The anti-break grid photovoltaic cell assembly according to claim 2, characterized in that: The material of the outer layer (323) of the electrode system (300) has a phase change temperature of 45-55° C. and a shape recovery rate of ≥98%.

4. The anti-break grid photovoltaic cell assembly according to claim 3, characterized in that: The wavy path of the secondary grid line (320) forms a gradually densified layout in the edge area of ​​the cell sheet, the gradient of the wave crest spacing variation of the gradually densified layout is 10-15 μm / mm, and the wave crest spacing in the edge area of ​​the photovoltaic cell sheet (200) is 60-70% of that in the central area.

5. The anti-break grid photovoltaic cell assembly according to claim 4, characterized in that: The middle layer (322) of the electrode system (300) comprises a bundle of carbon nanotubes arranged in a directional manner, and the arrangement direction forms an angle of ±15° with the extension direction of the gate lines.

6. The anti-break grid photovoltaic cell assembly according to claim 5, characterized in that: It also includes a micro stress buffer structure arranged at the intersection nodes of the main grid line (310) and a plurality of auxiliary grid lines (320), the structure being a hemispherical protrusion with a diameter of 50-80 μm and made of a composite material of silicone rubber and silver powder.

7. The anti-break grid photovoltaic cell assembly according to claim 6, characterized in that: The multi-layer composite structure of the secondary grid line (320) adopts a pulsed laser deposition process, with a laser energy density of 3-5 J / cm² and a pulse frequency of 100-200 Hz.

8. The anti-break grid photovoltaic cell assembly according to claim 7, characterized in that: It also includes a distributed optical fiber sensor integrated in the secondary grid line (320), with a sensor spacing of 2-5 mm, for real-time monitoring of grid line strain distribution.

9. The anti-break grid photovoltaic cell assembly according to claim 8, characterized in that: The wavy path of the secondary grid line (320) forms a light trap structure on the light-receiving surface of the photovoltaic cell (200), and the path curvature radius and the wavelength of the incident light satisfy a λ / 4 phase matching condition, where λ is the wavelength of the incident light, and by matching the peak wavelength of the solar spectrum, the value of λ is 500-800nm.

10. The anti-break grid photovoltaic cell assembly according to claim 9, characterized in that: The self-repairing coating (400) is coated on the surface of the grid line by an electrostatic spraying process, with a spraying voltage of 20-30 kV, a UV curing wavelength of 365 nm, and a curing time of 10-15 seconds; the wall thickness of the microencapsulated Ga-based liquid metal is 5-8% of the capsule diameter, and the wall material comprises alternately stacked polyurethane layers and gas-phase SiO2 layers.

Citation Information

Patent Citations

  • Photovoltaic cell and preparation method thereof

    CN114864707A

  • Photovoltaic cell and printing screen

    CN117832297A

  • Grid line structure, solar wafer and solar module

    CN205789999U

  • Anti-grid-breaking photovoltaic cell and anti-grid-breaking photovoltaic cell assembly

    CN219419045U

  • Photovoltaic element and method of producing photovoltaic element

    US20060260673A1

Cited By

  • Photovoltaic panel mounting structure of photovoltaic energy storage system

    CN122316199A